“Once I’m there I can find out where I am”: Place Making and the Homeless Geographies of a Downtown Toronto Street Kid Community - Bodner, John (Ethnologies, 2012)
Contemporary folklorists working on place have increasingly highlighted power and conflict as key aspects of spatial construction and the concomitant identity formation this practice provides. Utilizing this perspective and building on the work of social geographers’ research on the homeless I document the ways in which urban spatial regimes structure everyday practices of a street kid community in downtown Toronto. Utilizing the distinction between prime and marginal space to build an ecological map of the urban landscape I argue that my research participants’ utilization of de Certeau’s tactic of temporal manipulation claim public microsites for subsistence practices but reproduce their own esoteric subculture within marginal or refuse spaces that constitute a distinct backstage which rarely appears in the literature.